Infinitely many nodal solutions for anisotropic (p, q)-equations - Aizicovici, Sergiu (2022)
We consider an anisotropic (p.q)-Neumann problem with an indefinite potential term and a reaction which is only locally defined and odd. Using a variant of the symmetric mountain pass theorem, we show that the problem has a whole sequence of smooth nodal solutions which converge to zero in C1Ω.